Road Geometry Analysis on Jl. Nyi Ageng Serang, Sindangjawa, Dukupuntang District, Cirebon Regency, West Java STA 0+000 – STA 2+000 - Isradi, Muhammad; Nurulfiki, Hefa Wahyu; Badrudin, Ilman Nurhakim Firmasyah; Verdiansyah, Muhammad Dani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Nyi Ageng Serang Road is an important access road connecting several areas in Cirebon Regency. This study aims to analyze the suitability of the horizontal and vertical geometric elements of Nyi Ageng Serang Road, particularly in the segment from STA 0+000 to STA 2+000, against the applicable road planning standards, namely Regulation of the Minister of Public Works No. 19/PRT/M/2011 concerning Technical Requirements for Roads and Technical Planning for Roads. The research method used was a direct survey in the field to obtain primary data in the form of horizontal curve data, vertical slope, and other existing road geometric conditions. In addition, secondary data was obtained through literature studies and relevant supporting technical documents. The analysis was conducted by comparing existing geometric parameters, such as curve radius, transition curve length, maximum slope, and stopping sight distance, with applicable road technical standards, taking into account the planned speed according to road classification. The analysis results showed that several geometric elements on the road section from STA 0+000 to STA 2+000 did not fully meet planning standards. The discrepancies found include horizontal curve radii that are smaller than the minimum requirements, the presence of inadequate transition curves, and vertical gradients that exceed the maximum limits. These conditions have the potential to reduce the safety, comfort, and efficiency of road users' journeys. These findings are expected to form the basis for recommendations for road improvements in the future.